Duality Property of Discrete Quaternion Fourier Transform - Yudhiyanto Supriadi; Mawardi Bahri; Amir Kamal Amir (Department of Mathematics, Hasanuddin University, 2021)
We introduce the discrete quaternionic Fourier transform (QDFT), which is generalization of discrete Fourier transform. We establish the version discrete of duality property duality related to the QDFT.